1987
DOI: 10.1111/j.1600-051x.1987.tb02249.x
|View full text |Cite
|
Sign up to set email alerts
|

4 modalities of periodontal treatment compared over 5 years*

Abstract: The purpose of the present study was to assess in a clinical trial over 5 years the results following 4 different modalities of periodontal therapy (pocket elimination or reduction surgery, modified Widman flap surgery, subgingival curettage, and scaling and rool planing). 90 patients were treated. The treatment methods were applied on a random basis to each of the 4 quadrants of the dentition. The patients were given professional tooth cleaning and oral hygiene instructions every 3 months. Pocket depth and at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
201
2
14

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 315 publications
(239 citation statements)
references
References 21 publications
22
201
2
14
Order By: Relevance
“…Para las bolsas de clase I (1-3 mm), había una menor pérdida de inserción (0,5 mm) tras el RAR que con el tratamiento quirúrgico (TQ), mientras que no fue posible una disminución de la profundidad de sondaje tras los dos tratamientos (15,32,30,36).…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Para las bolsas de clase I (1-3 mm), había una menor pérdida de inserción (0,5 mm) tras el RAR que con el tratamiento quirúrgico (TQ), mientras que no fue posible una disminución de la profundidad de sondaje tras los dos tratamientos (15,32,30,36).…”
Section: Discussionunclassified
“…Por otro lado, estos mismos autores (29) revisando los estudios precedentes (13,15,28) reevaluaron la importancia de la PB inicial en relación a la capacidad de desbridamiento no quirúrgico, que parece ser más complicado de realizar en bolsas más profundas y, según lo hipotetizado por estos autores, lo que pudiera ocasionar una recurrencia de la enfermedad en menos tiempo.…”
Section: Escuela De Gothenburgunclassified
“…Periodontal treatment aims at achieving good oral hygiene conditions by removing all soft or hard deposits and their retention factors to reestablish the health of periodontal tissues, including alveolar bone tissue [22]. Thus, it is known that scaling and root planing play an important role in improvement of clinical and microbiological parameters [23,24].…”
Section: Discussionmentioning
confidence: 99%
“…2 Numerous studies have reported significant improvements of clinical and microbial parameters following nonsurgical periodontal therapy. [3][4][5][6] Despite the fact that non-surgical periodontal treatment may result in significant clinical improvements in the great majority of cases, evidence indicates that none of the currently available instrumentation techniques are effective in completely eliminating subgingival bacterial biofilm. 7 These limitations may be attributed to several factors such as the complex anatomy of teeth (i.e.…”
Section: Biological Rationalementioning
confidence: 99%